Pengaruh Mulsa Jerami Terhadap Laju Erosi Pada Tanah Mediteran - Parhadi, Parhadi (Politeknik Negeri Semarang, 2015)
In general, several factors that affect to erosion are climate, soil, topography, land cover and human activities. Erosion is a natural process which is difficult to be removed completely or zero erosion rate. Efforts to do is get the resulting erosion is still below the maximum threshold that does not exceed the rate of erosion of soil formation. One of the ways to control erosion is by providing ground cover with straw mulch. This study is aimed to determine the effect of straw mulch as a ground cover in mediterranean soil on the erosion rate. 4 The test was carried and for variations of rain intensity of 30 mm / hour, 40 mm / hour, 50 mm / hour and 60 mm / hour, 2 variations of slope 10o and 20o and the wide use of straw mulch is 4 tons / ha. Measurement of soil erosion is performed by putting the mediterranean soil with bulk 1.23 ton/m3 in to the 1m x 1m x 0,1 m box Then bombarded with rain simulation tool (rainfall simulator). Erosion measurements performed for conditions without mulch and the mulch. This research was done with physique model in Laboratory. The results of the research showed that straw mulch of 4 tonnes / ha can reduce soil erosion antd an average of 88. Use of Straw mulch of 4 tonnes / ha can also reduce the value of the cover factor with an average of 90%.